Compound sum distributions with dependence. Issue 2 (4th March 2021) - Nadarajah, Saralees; Kwong, Hok Shing; Tank, Fatih
Abstract : Compound sum distributions (in particular, the classical compound Poisson distribution) assume that claim amounts are independent and independent of the number of claims. These may not be realistic assumptions. In this note, formulas for compound sum distributions are derived for the general case of dependence. The influence of dependence on the distributions is investigated. A data illustration is given.